Recovery narratives: 'see how far i've come' - Richard Weingarten; Maria E. Restrepo-Toro (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2012)
As the paradigm shift towards a recovery-oriented mental health system becomes more prominent, individuals with lived experience of mental illness will continue to write and speak their narratives of mental illness and recovery. This article discusses the social reality of people with mental illness: how they are stigmatized by the media and how competing narratives within the mental health system afflict people with this disability. It also discusses the empowering process of constructing a narrative that enables the narrator/speaker to find meaning in her/his experience while putting a realistic 'face' on mental illness and recovery for the general public. It further describes how telling a narrative to diverse audiences, including a college class of 'people in recovery' enhances the author's personal recovery by giving his life new meaning and purpose.